Segitiga Hukum Internasional, Municipal dan Islam: Memahami Kompetisi, Interaksi dan Resolusi Hukum di Malaysia - Lukito, Ratno (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
As one of the Asian countries substantiating Islam as the official state religion, Malaysia always faces a dilemma in its encounter with international law, amid the dominance of municipal (national) and Islamic laws. Until now, many norms of international law seem to be apprehensively accepted. In fact, the existence of Islamic law, constitutionally recognized  as having an equal position with Common Law, often works as a barrier to the influence of international norms. Here, the segregation between British Common Law and Islamic law has played a major role in building the country's behavior in facing international law. Particularly, in redressing hard cases, international legal norms (such as international human rights law) are still difficult to get in and provide a positive influence in the national legal system. This paper focuses on the interaction between these three legal traditions of international, municipal and Islam in the face of rising Islamic conservatism supported by Malaysian Islamic parties in recent decades. Because legal segregation and compartmentalization between British common law and Islamic law had been chosen as the framework of legal pluralism in this country, the redress of the hard cases involving the meeting among the three laws --such as the case of apostasy, divorce due to apostasy, purdah etc.--, more often than not has led to the marginalization of international norms. This brings the consequence of the need to review the pattern of legal pluralism in this country, where relationship between different legal traditions is analyzed using bottom-up and non-state oriented perspectives. And it can only be done if the jurisprudence of legal pluralism in Malaysia can benefit the principles of Higher Law in its legal orientation; namely, the principles of universal justice, morality, and fairness, and not in the mere proximity to the character and the logic of official state law.